Monitoring the effect of integrated nutrient management practices on soil health in maize-based cropping system - Bamboriya, Jitendra Singh; Purohit, H. S.; Naik, B. Sri Sai Siddartha; Pramanick, Biswajit; Bamboriya, Shanti Devi; Bamboriya, Sumitra Devi; Doodhawal, Kiran; Sunda, Shankar Lal; Medida, Sunil Kumar; Gaber, Ahmed; Alsuhaibani, Amnah Mohammed; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2023)
Introduction Soil organic matter (SOM) plays a vital role in enhancing soil characteristics and promoting sustainable crop production. The active and passive components of SOM tend to be more effective indicators of soil changes than total SOM content. Methods This study aimed to examine the impact of integrated nutrient management (INM) on the active and passive segments of SOM in maize during the kharif seasons of 2019 and 2020 at the Instructional Farm of Rajasthan College of Agriculture, Udaipur. A total of 11 treatments comprising of control (no application of manures/fertilizers/biofertilizers), different INM combinations, and application of inorganic fertilizers were laid in a randomized block design (RBD) with three replications tested in this study. Results The use of INM through enriched phosphorus compost (EPC), biofertilizers, and chemical fertilizers significantly boosted both the active and passive constituents of the organic matter of the soil. In this study, a combination of 75% NPK fertilizers via soil test response (STR), EPC @ 5 t ha−1, an Azotobacter consortium, phosphorus solubilizing bacteria (PSB), and a foliar spray of 0.5% Zn considerably increased the active fraction of SOM than other treatments as indicated by microbial biomass carbon (251 mg kg−1), microbial biomass nitrogen (36.8 mg kg−1), microbial biomass phosphorus (6.82 mg kg−1), water-soluble organic carbon (73.9 mg kg−1), water-soluble carbohydrates (43.8 mg kg−1), presence of dehydrogenase in soil (6.82 μg TPF g−1 soil 24 h−1), and carbon mineralization (43.8 mg CO2C kg−1 soil 24 h−1). This treatment was also found to increase the passive fraction as shown by the presence of humic acid (0.332%), fulvic acid (0.210%), hymatomelanic acid (0.052%), brown humic acid (0.252%), and humin (0.604%). Discussion From this study, it can be concluded that the application of 75% NPK fertilizers as per STR + EPC + Azotobacter + PSB + 0.5% foliar Zn spray can improve soil health in maize-based cropping systems.